Carrier dynamics of two distinct localized centers in 530 nm InGaN green light-emitting diodes. (January 2018) - Li, Panpan; Bonef, Bastien; Khoury, Michel; Lheureux, Guillaume; Li, Hongjian; Kang, Junjie; Nakamura, Shuji; DenBaars, Steven P.
Abstract: We investigate carrier localization effect and recombination dynamics of 530 nm InGaN green light-emitting diodes (LEDs) using temperature-dependent photoluminescence (TDPL) and time-resolved photoluminescence (TRPL) methods. Two distinct emission peaks located in low-energy and high-energy sides were observed in PL spectrum at 10 K by Gaussian fitting. Both temperature-dependent blue-shift and TRPL decay time decreasing with photon energy of the two peaks indicate the presence of two localized states. Formation of In rich clusters in the InGaN wells was clearly observed by atom probe tomography (APT). Finally, the electroluminescent spectrum points out that both peaks originate from radiative recombination of localized states.